Hadis dari Masa ke Masa (Kodifikasi Era Mutaqaddimin) - Fatimah Fatimah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2020)
Hadith as the second Islamic teaching has a significant difference with the Qur'an in terms of official bookkeeping. In terms of the preservation of the Qur'an since the beginning of the Qur'an, there has been a decree to keep watch over and be protected from falsehood, but not with the Prophet's hadith. As before the reign of Caliph Umar bin Abdul Aziz even the writing or bookkeeping was prohibited. But after considering some of the impending advances if the hadith was not made up of books, the false hadiths would have arisen from irresponsible people, the death of the companions who had memorized the war, and dispersed the scholars to various territories with their death. Moreover, hadith memorization has become a tradition among the people and the fear of memorization has decreased. It was from these questions that the caliphate of Umar bin Abdul Aziz raised concerns about the bookkeeping in order to preserve and maintain its legitimacy. The official formulation of the hadith dates back to the second century H. under the command of Umar bin Abdul Aziz. Hadith as a teaching of Islam, produced various books of hadith scholars who were born mutaqaddimin and endowed. However in this article the author will focus more on the development of the books of the hadith in the mutaqaddimin period. The period of mutaqaddimin is the period between I H and the third century H, the opening of the hadith of the mutaqaddimin period from the end of the second century H to III H. In this period of mutaqaddimin the books of the hadith were born by the scholars including: first, the century to II H there are many scholars who produce the book of the hadith, among them the most famous is the book of hadith of the priest of Malik called the book of Muwaththa 'Malik. Secondly, in the third century H the books of the hadith were born including the Book of Sahih Bukhari, the Book of Muslim Tradition, the Book of Sunan Abu Dawud, the Book of Sunan At-Tirmidzi, the Book of Sunan An-Nasa'iy, the Book of Sunan Ibn Majah and others. The writing of this journal uses the library research method that the author has obtained from various reading sources related to this research.